Molecular and clinical aspects relevant for counseling individuals with clonal hematopoiesis of indeterminate potential - Cacic, Anna Maria; Schulz, Felicitas Isabel; Germing, Ulrich; Dietrich, Sascha; Gattermann, Norbert (Frontiers in Oncology, 2023)
Clonal hematopoiesis of indeterminate potential (CHIP) has fascinated the medical community for some time. Discovered about a decade ago, this phenomenon links age-related alterations in hematopoiesis not only to the later development of hematological malignancies but also to an increased risk of early-onset cardiovascular disease and some other disorders. CHIP is detected in the blood and is characterized by clonally expanded somatic mutations in cancer-associated genes, predisposing to the development of hematologic neoplasms such as MDS and AML. CHIP-associated mutations often involve DNA damage repair genes and are frequently observed following prior cytotoxic cancer therapy. Genetic predisposition seems to be a contributing factor. It came as a surprise that CHIP significantly elevates the risk of myocardial infarction and stroke, and also contributes to heart failure and pulmonary hypertension. Meanwhile, evidence of mutant clonal macrophages in vessel walls and organ parenchyma helps to explain the pathophysiology. Besides aging, there are some risk factors promoting the appearance of CHIP, such as smoking, chronic inflammation, chronic sleep deprivation, and high birth weight. This article describes fundamental aspects of CHIP and explains its association with hematologic malignancies, cardiovascular disorders, and other medical conditions, while also exploring potential progress in the clinical management of affected individuals. While it is important to diagnose conditions that can lead to adverse, but potentially preventable, effects, it is equally important not to stress patients by confronting them with disconcerting findings that cannot be remedied. Individuals with diagnosed or suspected CHIP should receive counseling in a specialized outpatient clinic, where professionals from relevant medical specialties may help them to avoid the development of CHIP-related health problems. Unfortunately, useful treatments and clinical guidelines for managing CHIP are still largely lacking. However, there are some promising approaches regarding the management of cardiovascular disease risk. In the future, strategies aimed at restoration of gene function or inhibition of inflammatory mediators may become an option.